STRATIGRAPHIC DISTRIBUTION OF MACERALS AND BIOMARKERS IN THE DONETS BASIN: IMPLICATIONS FOR PALEOECOLOGY, PALEOCLIMATOLOGY AND EUSTACY - Izart A.; Elie M.; Alsaab D.; Sachsenhofer R.F.; Rainer T.; Sotirov A.; Zdravkov A.; Privalov V.A.; Antsiferov V.A.; Panova E.A.; Zhykalyak M.V. (My University, 2006)
More than one hundred and thirty coal seams and coaly layers occur in the Donets Basin (Donbas). Twenty-eight (52 samples) of them, ranging in age from Serpukhovian (Late Mississipian) to Gzhelian (Late Pennsylvanian), 33 clastics and three limestones were studied in terms of maceral composition, sulphur contents, and biomarker distribution. Diterpanes are used to estimate the contribution of different groups of plants and the height of the water table in the swamp; hopanes are a measure of bacterial activity in the peat; and steranes indicate the relative input of wood and algae. Stratigraphic trends in these parameters are discussed in relation to paleoenvironment, climatic changes, and eustacy. A tropical climate prevailed in the Donbas from Serpukhovian to Kasimovian times. Nevertheless, periods with drier and wetter conditions can be distinguished based on maceral and biomarker data. Relatively dry conditions are observed during Serpukhovian and Vereian times, whereas wetter climates with a maximum of coal deposition occurred during the (late) Bashkirian, most of the Moscovian, and the earliest Kasimovian. No economic coal seams are hosted in upper Kasimovian and Gzhelian deposits, a result of a change to an arid climate. Our data also suggest climatic changes during sequences of different order. For the second-order, third-order, and fourth-order sequences, relatively dry or wet conditions occurred during coal deposition in the lowstand systems tract, an intermediate climate during the transgressive systems tract and the maximum flooding, and a wet climate during the highstand systems tract. The results for high frequency sequences support the Cecil's paleoclimatic model: an intermediate paleoclimate during LST (sandstone and levee siltstone), a wet climate during early TST (coal), and a dry climate during late TST (limestone), MFS (claystone), and HST (deltaic siltstone). Coals deposited during maximum flooding periods are more enriched in C27 steranes derived from algae, and contain lower proportions of C29 steranes derived from the wood of higher plants. © 2005 B.V. All rights reserved.
Keywords: CARBONIFEROUS; COAL PETROGRAPHY; MOLECULAR GEOCHEMISTRY; ORGANIC GEOCHEMISTRY; UKRAINE; Paleozoic::Carboniferous; Палеозой::Каменноугольная